Starch films cross-linked with boronated chitosan enriched with cannabis oil as food packaging material - Kinga Mylkie; Dorota Chełminiak-Dudkiewicz; Dariusz T. Młynarczyk; Aleksander Smolarkiewicz-Wyczachowski; Marta Ziegler-Borowska (Polymer Testing)
Recent advancements in biopolymer-based packaging materials are transforming sustainable packaging, particularly through innovative approaches to enhancing starch, a promising biodegradable polymer. While starch offers several advantageous properties for food packaging, its practical application is hindered by poor vapor barrier performance, low mechanical and thermal strength, brittleness, and hydrophilicity due to strong inter- and intramolecular interactions. We introduced a novel cross-linking strategy using boron-containing materials to address these limitations. Starch films containing cannabis oil (3 % w/w) (CBD-S) were further enhanced through crosslinking with chitosan functionalized with boronic acid (Cs-FPBA-CBD-S). Crosslinking starch with boronic acid-functionalized chitosan improved the films' hydrophobicity, significantly reducing the water vapor transmission rate (WVTR) from 5 g/m2·day (for the CBD-S film) to 3 g/m2·day (for the Cs-FPBA-CBD-S films). Mechanical testing showed that crosslinking mitigated moisture-induced weakening of the films. In wet conditions, tensile strength dropped from 2.9 to 1.2 MPa in CBD-S and 3.6 to 1.9 MPa in Cs-FPBA-CBD-S. Young's modulus also decreased less in the cross-linked films. After 10 days of dry storage, they retained elasticity and structure despite a 25 % stress loss, confirming improved durability. Based on boronic acid-functionalized chitosan, this crosslinking mechanism notably enhanced the material's antioxidant activity, with a significant increase in scavenging capacity (from 65 % to 74 %) and enhanced thermal stability. Moreover, these films showed accelerated biodegradation, reaching 80 % degradation after 30 days compared to unmodified starch, and showed strong antibacterial properties against A. fisheri (Gram-negative bacteria) as assessed using the Microtox® test.